2017
DOI: 10.1108/intr-04-2016-0091
|View full text |Cite
|
Sign up to set email alerts
|

Why users purchase virtual products in MMORPG? An integrative perspective of social presence and user engagement

Abstract: Purpose Prior studies on virtual product purchase have focused on external technological factor but have paid less attention to internal user factors. Thus, drawing upon the social presence and user engagement theories, the purpose of this paper is to develop a research model considering both technological factors and user factors and empirically examine the validity of the proposed research model. Design/methodology/approach A survey from 214 World of Warcraft players was conducted to test the proposed rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
92
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(97 citation statements)
references
References 77 publications
2
92
1
2
Order By: Relevance
“… Content analytic 48 N/A N/A Gambl. PG forum Jin et al ( 2017 ) Quantit. Cross-sectional 214 < 21–36+ 8.4% Gaming MMORPG Kaptein et al ( 2015 ) Quantit.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… Content analytic 48 N/A N/A Gambl. PG forum Jin et al ( 2017 ) Quantit. Cross-sectional 214 < 21–36+ 8.4% Gaming MMORPG Kaptein et al ( 2015 ) Quantit.…”
Section: Resultsmentioning
confidence: 99%
“…According to reviewed studies, online gaming communities inherently exist inside the game. This is especially true with MMORPGs (Badrinarayanan et al 2014 , 2015 ; Ben-Ur et al 2015 ; Fang et al 2009 ; Gui 2018 ; Hota and Derbaix 2016 ; Jin et al 2017 ; Park et al 2018 ; Pinto et al 2015 ). MMORPG playing typically takes place in guilds, that is, long-lasting social groups where players collaborate in order to better game success.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, a large portion of the revenue of MMORPG providers depends on their sales of virtual in-game accessories (e.g., weapons and food) rather than the purchase price of the title itself (Nojima, 2007), because virtual in-game accessories indicate different levels of skill and ability, and all of which may be carried over into subsequent gaming sessions (Wu, Chen, & Cho, 2013). This is also why MMORPGs attract a huge amount of loyal users who are willing to pay money for virtual items when compared with other kinds of online games (Jin, Sun, Wang, & Zhang, 2017). Thus, the pricing strategy of such online games as MMORPG has significant differences when compared with traditional industrial products or even most typical digital products (e.g., software, music; Ke, Ba, Stallaert, & Zhang, 2012).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Moreover, empirical research on social interactions in MMORPGs has demonstrated that in-game social interactions are an important element in promoting players' enjoyment (Cole and Griffiths, 2007;Jia et al, 2015;Lin et al, 2015) and continuance intention to play (Chang et al, 2014). Another study on MMORPGs reported a positive relationship between players' in-game social interactions and their intention to purchase virtual products ( Jin et al, 2017). Therefore, we infer that players are willing to pay more in MMORPGs when they develop a high-density network in the game.…”
Section: Research Hypothesesmentioning
confidence: 99%